Evaluación de dos protocolos de IATF con progestágenos en Belisario Quevedo. - Vásquez Conza, Yajaira Lizeth (2021)
The research project is carried out at the “POTRERILLOS” farm located in the Province of Cotopaxi, Latacunga canton, Belisario Quevedo Parish, during the months of December 2020 - January 2021; The objective of this work is to evaluate an IATF (Fixed Time Artificial Insemination) protocol with the use of progestogens with a variant of estradiol benzoate and equine chorionic gonadotropin post removal of the intravaginal device in cattle to increase the number of pregnant females in a short time. Selecting 14 little cows by lacing, the materials be used are the following: intravaginal devices with progesterone "CIDR", estradiol benzoate, Prostaglandin, Equine Chorionic Gonadotropin. For this research, it is divided into two study groups, for both groups the cows undergo a gynecological check-up to rule out reproductive pathologies, pregnancies, their body condition is also taken into account. For group N ° 1: 7 little cows were used, their protocol to follow is the following on day 0, the CIDR (1.38gr) is placed and 2 mg estradiol benzoate (IM) is administered; day 8 the CIDR is removed and prostaglandin (IM) is administered; day 9, 1mg of estradiol benzoate is administered IM) and on day 10, Fixed Time Artificial Insemination is performed. Meanwhile, for Group N ° 2, 7 little cows are used, the protocol to be followed is similar to the first group with the difference that on day 9, 200 IU of Equine Chorionic Gonadotropin (IM) is administered. The pregnancy diagnosis is made by rectal palpation at 45 days, after artificial insemination at a fixed time. The following characteristics were evaluated: Body condition of the animals in IATF, cyclicity of the animals before the IATF, presence of heat, time of heat in the animals, pregnancy by rectal palpation and cost-benefit.